Hiranyavarna Mahavihara: its Role and Relation with Nagabaha - Bajracharya, Ranjana (Tribhuvan University Journal, 2010)
Not available. Key words: Hiranyavarna Mahavihara; Nagabaha Tribhuvan University Journal Vol. XIX, 1996 Page: 141-148 Uploaded Date: 24 Nov., 2010